Risk Factors of Angiographic Recurrence After Endovascular Coil Embolization of Intracranial Saccular Aneurysms: A Retrospective Study Using a Multicenter Database - Tian, Zhongbin; Liu, Jian; Zhang, Ying; Zhang, Yisen; Zhang, Xiaolong; Zhang, Hongqi; Yang, Ming; Yang, Xinjian; Wang, Kun (Frontiers in Neurology, 2020)
Background: Endovascular therapy of intracranial aneurysms has a high recurrence rate. This study aimed to evaluate the risk factors of recurrence after endovascular coil embolization of intracranial aneurysms. Methods: From January 2014 to May 2015, 504 patients with 558 intracranial aneurysms who were treated by endovascular therapy were recruited from four high-volume centers. We used multivariate Cox proportional hazard regression to evaluate the risk factors associated with the angiographic recurrence of intracranial saccular aneurysms after endovascular coil embolization. Results: Angiographic follow-up was available for 504 patients (558 aneurysms), with a mean duration of 11.42 months. Of the 558 aneurysms, 57 (10.2%) aneurysms showed recurrence. Aneurysm size (p=0.028), therapy (non-stent assisted coiling or stent-assisted coiling) (p=0.008), the Raymond scale (p=0.040), aneurysm rupture status (p<0.001), and packing density (p<0.001) showed significant associations with angiographic follow-up outcome. A low packing density was independently associated with aneurysmal recurrence after multivariate Cox proportional hazard regression analysis (p<0.001). Conclusion: Endovascular treatment is effective for these lesions. Multiple factors could attribute to the aneurysmal recurrence after endovascular coil embolization. The low packing density is the independent risk factor for aneurysmal recurrence. These findings should be verified by larger multicenter and multi-population studies.